JAMINAN TERHADAP KEBEBASAN BERAGAMA DI INDONESIA - Romli Mubarok (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Indonesia is a country that recognizes freedom of religion, even placing it as something that is constitutive and binding. In order for the spirit of the constitution that will be maintained, setting the country in terms of religious life is still needed. This is manifested in making laws about religion. Normatively, guarantees freedom of religious life in Indonesia is actually quite strong. However, implementation is still not optimal. There are so many Indonesian citizens who feel restrained freedom of religion and belief. The state has set about religious freedom, clause 28E article (2) and clause 29 article (2) of the UUD 1945. In this article every citizen be given the freedom to choose religion and practicing religion. Thus, the Indonesian government has made efforts in fostering religious life as well. In addition the government has poured about the desecration of religious rule in clause 1 of UU No. 1/PNPS/1965 which states seek public support for the ban and doing something interpretation of religion.